Magnesium uptake by connecting fluid-phase endocytosis to an intracellular inorganic cation filter - Sandra H. Klompmaker (Nature Portfolio, 2017)
Metal bioavailability is frequently limited by sequestering agents which makes them inaccessible to cells. Here the authors show that cells can increase Mg2+ uptake via fluid phase endocytosis and accumulate this metal in their vacuole loaded with polyphosphate, and later can be exported to the cytosol.